เภสัชจลนศาสตร์ประชากรของยาเมอโรพีเนมในผู้ป่วยทารกขั้นวิกฤต - วัลย์ลิกา ยนต์วิเศษ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
Objectives: This study aimed to determine the population pharmacokinetic parameters of meropenem and evaluate the covariates affecting population pharmacokinetic parameters in critically ill infants.Methods: A prospective study was conducted from February 2020 and February 2021 in thirty-five critically ill infant patients between the ages of 1 month to 2 years treated with meropenem at King Chulalongkorn Memorial Hospital in Thailand. A total of 160 free concentrations of meropenem were quantified using a validated high-performance liquid chromatography with ultraviolet (HPLC-UV) detection. Population pharmacokinetics of meropenem were analyzed by the non-linear mixed-effect modeling using NONMEM software. Internal validation methods, including bootstrapping and prediction-corrected visual predictive check (pcVPC), were applied to evaluate the robustness and predictive power of the final model. Results: A one-compartment model with first-order elimination showed the best fit to the data. The population clearance (CL) and population volume of distribution (Vd) values were 1.33 L/h and 2.27 L, respectively. Weight and creatinine clearance (CRCL) were influential covariates for CL, while weight was the significant covariate for Vd of meropenem. From the base to the final model, the inter-individual variabilities in CL and the Vd were significantly reduced. The model evaluation results suggested robustness and good predictability of the final model. Conclusions: A population pharmacokinetic model of meropenem in critically ill infant patients was developed and validated.  CRCL and weight were identified as significant covariates. The population pharmacokinetic model could be used to recommend the dosage individualization of meropenem in institutions with similar patient population characteristics.